2021
DOI: 10.1016/j.ctro.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound delta-radiomics during radiotherapy to predict recurrence in patients with head and neck squamous cell carcinoma

Abstract: This study investigated the use of quantitative ultrasound (QUS) obtained during radical radiotherapy (RT) as a radiomics biomarker for predicting recurrence in patients with node-positive head-neck squamous cell carcinoma (HNSCC). Methods: Fifty-one patients with HNSCC were treated with RT (70 Gy/33 fractions) (±concurrent chemotherapy) were included. QUS Data acquisition involved scanning an index neck node with a clinical ultrasound device. Radiofrequency data were collected before starting RT, and after we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Studies that recognize tumor recurrence in follow-up images have gradually become apparent. US-based radiomic features can identify recurrence risk in patients with head-neck squamous cell carcinoma treated with RT ( 130 ). Glioblastoma multiforme has a poor prognosis and inevitably recurs or progresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that recognize tumor recurrence in follow-up images have gradually become apparent. US-based radiomic features can identify recurrence risk in patients with head-neck squamous cell carcinoma treated with RT ( 130 ). Glioblastoma multiforme has a poor prognosis and inevitably recurs or progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Fatima et al. ( 130 ) performed radiomic analysis of US images of patients with head and neck squamous cell carcinoma to assess the recurrence status after RT. The best-selected SVM model achieved AUC and accuracy of 75% and 81% at week 1 and 80% and 82% at week 4, respectively.…”
Section: Some Case Studies and Applicationsmentioning
confidence: 99%
“…124,125 Delta radiomics has been proven effective in the study of immunotherapy response 126,127 or to predict recurrence in oncological patients. 128…”
Section: Delta Radiomicsmentioning
confidence: 99%
“…Several studies have demonstrated the utility of QUS imaging in predicting treatment response using pretreatment imaging features [ 12 , 14 , 15 , 16 ]. Similarly, the acquisition of QUS features during different treatment modalities (chemotherapy, radiotherapy) reflects ongoing microstructural changes resulting from cell death and can effectively improve the interpretation of clinical outcomes [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%